2016
DOI: 10.1097/mao.0000000000000908
|View full text |Cite
|
Sign up to set email alerts
|

Language Development in the First Year of Life

Abstract: During the first 12 months, typically developing infants exhibit advances in speech segmentation, word learning, syntax acquisition, and communication, both verbal and nonverbal. Infants and their caregivers coconstruct a communication foundation during this time, supporting continued language growth. The language outcomes of hearing children are robustly predicted by their experiences and acquired competencies during the first year; yet these predictive links are absent among prelingually deaf infants lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 113 publications
0
34
0
Order By: Relevance
“…Fagan, Bergeson, and Morris (2014) found that mothers of children with CI also use more directives (e.g., "say," "cat," "sit here") and prohibitions (e.g., "no," "don't open it") than mothers of age-matched hearing children. Thus, as a group DHH children experience a reduced and less demanding communication interaction with primary caregivers (Levine, Strother-Garcia, Hirsh-Pasek, & Golinkoff, 2016). Although this experience undoubtedly contributes to a language development delay, we propose that it also impacts on the development of early EF abilities as it offers far fewer opportunities for self-planning, inhibition, and control of interactions by DHH children.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Fagan, Bergeson, and Morris (2014) found that mothers of children with CI also use more directives (e.g., "say," "cat," "sit here") and prohibitions (e.g., "no," "don't open it") than mothers of age-matched hearing children. Thus, as a group DHH children experience a reduced and less demanding communication interaction with primary caregivers (Levine, Strother-Garcia, Hirsh-Pasek, & Golinkoff, 2016). Although this experience undoubtedly contributes to a language development delay, we propose that it also impacts on the development of early EF abilities as it offers far fewer opportunities for self-planning, inhibition, and control of interactions by DHH children.…”
Section: Discussionmentioning
confidence: 84%
“…The quality of parent-child interaction is perhaps more important for language and EF development in DHH children. The developmental delays caused by early language deprivation could be compounded by the negative effects of a communication-poor environment (see Levine et al, 2016). The inclusion of the DHH group allows us to evaluate the developmental impact of these early experiences when they are curtailed because of barriers to communication in deafness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, visual reception (VR) begins to develop at birth and by approximately 6-months of age, infants exhibit similar patterns of visual preference and visuospatial organization as adults (Deen et al, 2017;Emberson, Richards, & Aslin, 2015). On the other hand, advances in communicative development begin to emerge later and are most prominent by 12-months of age (e.g., Levine, Strother-Garcia, Golinkoff, & Hirsh-Pasek, 2016).…”
Section: Cognitive Development In Infancy and Periods Of Sensitivitymentioning
confidence: 99%
“…Language covers a complex set of abilities that can be classified as receptive and expressive (1) . These abilities can be functionally described as listening and speaking behaviors, as they occur under some conditions and produce consequences.…”
Section: Introductionmentioning
confidence: 99%
“…To act as listener and as speaker are distinct verbal abilities, established by different teaching conditions and, therefore, are initially independent (2,3) . The speech sound processing starts even before the birth and the deprivation of access to speech sounds at the first years of life compromises the typical development of the oral language (1) , affecting the global development and life quality (4) .…”
Section: Introductionmentioning
confidence: 99%